Research and Evaluation of Methods for Determining Deformation Modulus of A Base Course of Road Pavement - Lina Bertulienė; Alfredas Laurinavičius; Audrius Vaitkus (The Baltic Journal of Road and Bridge Engineering)
The continuously increasing need for the strengthening of road pavement structures in Lithuania induces to implement new road reconstruction technologies, to look for new alternatives in laying structural pavement layers, to carry out research of road pavement structures in their real operational conditions. This article studies methods for determining structural pavement strength, assesses the strength measuring devices using static and dynamic methods. In order to identify and compare the accuracy of test data collected by using static and dynamic methods the comparative measurements were carried out on a base course of experimental road section by four measuring devices, i.e. static beam Strassentest, dynamic devices ‒ ZORN ZSG 02, light weight deflectometer Prima 100 and falling weight deflectometer Dynatest 8000. Further results of the research of this experimental road section, analysis and evaluation of these results will enable to select the most suitable measuring method for each structural pavement layer.